Upper Egypt--Challenges and Priorities for Rural Development - World Bank (Washington, DC, 2014)
This sector report on Challenges and Priorities for Rural Development analyzes why Upper Egypt has lagged behind the rest of the country and to help the Government of Egypt and stakeholders to define a framework for interventions to promote broad-based economic growth and human development that will reach the poor and improve welfare in rural Upper Egypt. To achieve this objective, the strategic framework for intervention proposed here has two dimensions. The first is to foster broad-based economic growth based on agricultural development and off-farm activities. The second is to enhance access to basic infrastructure and services by promoting local level planning and civil society engagement.